Georgia : Technical Assistance Report-Enhancing the Fiscal Rules. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the recommendations made by the IMF mission to assist Georgian authorities in enhancing country's fiscal rules framework. It is recommended that the fiscal rules should consider both the overall objectives and the economic context in which they are applied. In Georgia, this would include: the stated primary objective of fiscal sustainability as well as the need for flexibility to respond to economic shocks; the transitional nature of the Georgian economy; and the intension to gradually move toward the European Union fiscal governance framework. It is also recommended that the fiscal policy targets should factor in potential economic shocks and fiscal risks.